Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Belanja Daerah terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Provinsi Sumatera Barat - Berti Indah Sari; Halma wati (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to examine the effect of local revenue, general allocation funds and regional spending on the financial performance of local governments. The sample used in this study were districts / cities of West Sumatra Province with 12 districts and 7 cities in West Sumatra. The data used in this study is the data on the realization of the District / City APBD in West Sumatra Province for the 2015-2018 fiscal year. This research uses descriptive statistical data analysis techniques, classical assumption test, multiple linear regression analysis, hypothesis testing and determination coefficient test. The results showed that the Regional Original Revenue, DAU and Regional Expenditures together had a significant positive effect on Regional Government Financial Performance. The test results are in accordance with the previous theory and hypothesis which states that PAD, DAU and Regional Expenditures have a significant positive effect on the financial performance of local governments.